RELATIONSHIP OF BODY MASS INDEX WITH OVARIAN RESERVE STATUS OF INFERTILE WOMEN MEASURED BY ANTI-MÜLLERIAN HORMONE LEVEL - Parveen, Naila; Sheikh, Shehnaz; Javed, Shireen (Pakistan Journal of Physiology, 2014)
Background: Infertility is believed to be more in obese than normal women. Anti-Müllerian hormone has been used as an index of ovarian reserve. The objective of this study was to see the relationship of body mass index with serum Anti-Müllerian hormone levels in infertile women of reproductive age. Methods: This cross-sectional study was conducted at Infertility Clinic of Obs/Gyn Unit-II, Civil Hospital, Karachi from Oct 2011 to Oct 2012. Fifty-two infertile women aged 20–35 years were selected from the Out-patient Department. Height and weight was measured in all participants. Body mass index was then calculated. The patients were sub-classified according to body mass index classification for Asian population. Blood samples to estimate Anti-Müllerian hormone levels were obtained irrespective of the day of menstrual cycle. On the basis of Anti-Müllerian hormone levels, infertile women were grouped into normal ovarian reserve (Anti-Müllerian hormone ≥1.25 ηg/L) and diminished ovarian reserve (Anti-Müllerian hormone ≤1.25 ηg/L). Results: Increased mean values of body mass index were found in diminished ovarian reserve group compared to normal ovarian reserve group. Inverse significant correlation was found between body mass index and Anti-Müllerian hormone level in diminished ovarian reserve group. Conclusion: Serum Anti-Müllerian hormone has significant negative association with body mass index in infertile women having diminished ovarian reserve. Pak J Physiol 2014;10(1–2):25–7